Identifying Conflicts of Interest in Therapeutic Massage and Bodywork Research - Porcino, Antony J. (Multimed Inc., 2013)
Identifying and addressing forms of bias in research are critical to the integrity and value of research. Conflicts of interest are an important aspect of research that must be addressed equally to any other form of research bias. Conflicts of interest occur when the judgment of a party involved in the research, either a researcher or a treatment provider, may be compromised by more than one interest relative to the research. As therapeutic massage and bodywork (TMB) is a younger field of research, some forms or aspects of conflicts of interest may not be understood. This editorial explores the meaning of conflicts of interest, how to increase awareness of them, and facets of research specific to TMB that may create such conflicts. Full disclosure in grant applications and manuscripts is critical to ensure that grantors, reviewers, and users of research are better informed of potential conflicts of interest, can understand the steps taken to manage the conflicts, and ultimately can better assess the research integrity and value.